ANALISIS PENGARUH KEMANDIRIAN KEUANGAN DAERAH KOTA PALANGKA RAYA - Talia, Nana; Hukom, Alexandra (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The aim of this research is to examine how Local Own-source Revenue (PAD), Regional Expenditure, and Regional Financing impact the financial independence of Palangka Raya City. In this context, financial independence is defined as the ability of local government to generate revenue autonomously while reducing dependency on income from external sources. This study employs Local Own-source Revenue (PAD), Regional Expenditure, and Regional Financing as independent variables. The cause-and-effect relationship between the independent variables and regional financial independence is evaluated using path analysis.The research findings indicate a significant relationship between PAD, Regional Expenditure, and Regional Financing with regional financial independence. PAD and Regional Expenditure have a significant positive influence on regional financial independence, while Regional Financing shows a significant negative influence. These findings provide valuable insights for local governments in formulating more effective fiscal policies to enhance regional financial independence.